Chemical constituents from the branches and leaves of Amorpha fruticosa L. and their chemotaxonomic significance - Liang Li; Mingxia Li; Haiyuan Yu; Yanan Liu; Zhicheng Guo; Li Quan; Ziyuan Zhao; Jinfeng Sun; Wei Zhou; Tieqiang Zong; Gao Li (Biochemical Systematics and Ecology, 2026)

Electron‑flow‑driven synergistic mineralization of naphthalene by an S‑N‑doped biochar‑bridged engineered consortium - Fuliang Bai; Chao Yang; Ze Yu; Zeya Wu; MingXia Sun (Journal of Hazardous Materials, 2026)

A diatom-inspired tissue adhesive for wound sealing and hemostasis under extreme physiological conditions - Furui Qu; Xiaojie Sun; Mingxia Feng; Xiaoye Wang; Yan Zhang; Zicheng Xia; Yang Yang; Xiguang Chen; Na Li; Chao Feng (Chemical Engineering Journal, 2026)

Effect of biochar application method on soil NH3 volatilization and ureolytic microbial community in an upland soil - Juying Liu; Rui Zhao; Meiqi Zhang; Mingxia Pan; Xuedong Dai; Ning Yang; Qiang Sun; Tianyi He; Zhengfeng An; Osipiuk Karol; Zunqi Liu (Applied Soil Ecology, 2026)

Neurospora intermedia for single-cell protein production: Enhancement by medium optimization and atmospheric and room temperature plasma mutagenesis - Haifeng Zhao; Shichuang Sun; Mengru Jin; Junlong Li; Mingxia Li; Li Wang; Wei Zhang; Mengjie Wang; Rugang Zhu; Tiejing Li; Jialu Cao; Dingrong Kang (Bioresource Technology, 2026)

Pyrene trisulfonic acid-functionalized silica-based multi-mode stationary phase for separation of hydrophilic, hydrophobic compounds and rare earth ions - Yali Yang; Hui Ding; Kaijun Quan; Hongwei Zhao; Mingxia Sun; Zhimin Yang; Xiuhui Liu; Hongdeng Qiu; Jia Chen (Analytica Chimica Acta, 2026)

Defect engineering synergised with S-scheme heterojunction for the efficient reduction of carbon dioxide - Jie Gu; Mingxia Tian; Yuan Zhang; Lili Huang; Beibei Sun; Yong Qin; Jianhui Jiang (Process Safety and Environmental Protection, 2026)

Magic chain-flip triboelectric nanogenerator for multi-mode wind and raindrop energy harvesting - Mingxia Chen; Jiahong Yang; Rui Gu; Hai Yan; Zhenghao Li; Siqi Sun; Nuo Xu; Ziwei Huo; Zhong Lin Wang; Qijun Sun; Xiangde Lin (Chemical Engineering Journal, 2026)

Two new phenolic glycosides from the roots of Iris domestica (L.) Goldblatt & Mabb and their cytotoxic activity - Tieqiang Zong; Lantian Cui; Jinfeng Sun; Zhengyu Hu; Pengcheng Yang; Mingxia Li; Mei Jin; Wei Zhou; Gao Li (Natural Product Research, 2026)

Chemical constituents from the dried root bark of Lycium chinense Mill. and their chemotaxonomic significance - Mingxia Li; Tieqiang Zong; Yanan Liu; Jinfeng Sun; Zhengyu Hu; Long Jin; Mei Jin; Wei Zhou; Gao Li (Biochemical Systematics and Ecology, 2026)

Level measurement and influencing factor analysis of agricultural sustainable development in Shandong Province, China - Ruili Zheng; Xinnuo Liu; Zhien Gao; Zongbin Ma; Mingxia Zhang; Zhuyuan Sun; Dongyun Yan (Environment, Development and Sustainability, 2025)

One new isoprenylated resorcinoid and one new chromene meroterpenoid with potential anti-inflammatory effects from the leaves of Rhododendron dauricum L - Tieqiang Zong; Yongkang Xue; Mei Jin; Chao Ye; Jinfeng Sun; Lantian Cui; Zhengyu Hu; Mingxia Li; Pengcheng Yang; Wei Zhou; Gao Li (Natural Product Research, 2025)

Silicified microscale zero-valent iron for in situ remediation of chloramphenicol in groundwater: Reactivity coupling with mobility - Lu Liu; Yue Meng; Qiyue Zhang; Yuanyuan Sun; Minda Yu; Mingxia Zheng (Chemical Engineering Journal, 2025)

Room-temperature fabrication of layer-by-layer assembled aromatic phosphonium ionic organic single crystals for efficient environmental remediation: iodine capture and thorium(IV) sequestration - Mingxia Sun; Jia Chen; Ting Zhang; Jing He; Yunyun Zhang; Huifeng Liu; Wei Xu; Zhao Wang; Hongdeng Qiu (Chemical Engineering Journal, 2025)

Pre-harvest sprouting in cereals: Global incidence, impacts and mitigation strategies - Rui Yang; Matthew Tom Harrison; Yinmiao Yang; Chunhu Wang; Sergey Shabala; Mingxia Huang; Chenchen Zhao; Meixue Zhou; Chengming Sun; Ke Liu (Field Crops Research, 2025)

Crystallization regulation and defect passivation of perovskite films via resonance-structured ionic additive for high-performance solar cells - Guogen Huang; Yuqing Dong; Guanlin Li; Zebing Gao; Chuanlin Gao; Kangbo Sun; Haoxuan Zeng; Haohua Wu; Jinxing He; Xinting Wang; Qing Bai; Tong Shan; et al. (Chemical Engineering Journal, 2025)

Terahertz metasurface biosensor empowered by quasi-bound states in the continuum for label-free identification of different cancers and trace molecular sensing - Shuocheng She; Jiachen Zuo; Yang Li; Liu Sun; Zekun Yang; Yaowei Dai; Fan Yang; Yizhu Zhang; Mingxia He (Chemical Engineering Journal, 2025)

From isolation to connectivity: A graph theory approach for optimising karst protected areas using an umbrella species - Mingxia Zhang; Xuanyuan Liu; Wenmin He; Alice C. Hughes; Wenqin Li; Jiahao Sun; Changyong Ma; Qihai Zhou (Biological Conservation, 2025)

Efficient catalytic degradation and detoxification of 6PPD-quinone by the multifunctional enzyme system of phanerochaete chrysosporium - Haiyang Yu; Li Luo; Baihui Wu; Jiaxuan He; Hanbing Wang; Rongbing Chen; Mingxia Ji; Qinsi Yang; Guoming Zeng; Wei Wu; Da Sun (Journal of Hazardous Materials, 2025)

Nano biochar enhances organic carbon accumulation, molecular complexity, and salt leaching in saline–alkali soil columns - Yue Xie; Tiantian Bai; Yongqi Zhang; Benhua Sun; Mingxia Gao; Hao Feng (Journal of Environmental Management, 2025)

In silico identification for flavor antioxidant compounds in Chrysanthemi flos uncovers the interactions between saccharides and secondary metabolites - Jiamu Ma; Le Wang; Mingxia Li; Jianling Yao; Wei Liu; Feng Zhang; Mengyu Sun; Yu Cao; Yuqing Yang; Yongqi Yang; Letian Ying; Meng Shen; et al. (Food Chemistry, 2025)

In-situ passivation of perovskite films by parallel surface adsorption of dual-active-site ammonium cations for high-performance inverted perovskite solar cells - Guanlin Li; Zebing Gao; Guogen Huang; Jinxing He; Kangbo Sun; Xinting Wang; Haohua Wu; Chuanlin Gao; Xianghui Zeng; Xianfang Zhou; Hanlin Hu; Yunfei Hu; et al. (Chemical Engineering Journal, 2025)

Spectral and molecular insights into the variations of dissolved organic matter in shallow groundwater impacted by surface water recharge - Hongyu Ding; Mingxia Zheng; Lina Yan; Xiaoyu Zhang; Lu Liu; Yuanyuan Sun; Jing Su; Beidou Xi; Huibin Yu (Water Research, 2025)

Corrigendum to “The C3d-fused Porcine Circovirus Type 2d virus-like particle induced early and enhanced immune response and protected pigs against challenge” [Vet. Microbiol. 299 (2024) 110305] - Xinyu Qi; Zheng Fang; Liang Meng; Xuyan Xiang; Yan Ju; Xuehui Cai; Tongqing An; Mingxia Sun; Haiwei Wang (Veterinary Microbiology, 2025)

Correlation analysis and modeling application from objective indicators to subjective evaluation of scented tea: A case study of rose tea - Ruolan Song; Meng Shen; Yanran Wang; Youyi Sun; Jiamu Ma; Qingyue Deng; Xueyang Ren; Xianxian Li; Yuan Zheng; Yingyu He; Feng Zhang; Mingxia Li; et al. (Food Chemistry, 2025)

The C3d-fused Porcine circovirus type 2d virus-like particle induced early and enhanced immune response and protected pigs against challenge - Xinyu Qi; Zheng Fang; Liang Meng; Xuyan Xiang; Yan Ju; Xuehui Cai; Tongqing An; Mingxia Sun; Haiwei Wang (Veterinary Microbiology, 2024)

Spectral and molecular insights into the characteristics of dissolved organic matter in nitrate-contaminated groundwater - Hongyu Ding; Huan Gao; Mingtan Zhu; Minda Yu; Yuanyuan Sun; Mingxia Zheng; Jing Su; Beidou Xi (Environmental Pollution, 2024)

Insight into spatial variations of DOM fractions and its interactions with microbial communities of shallow groundwater in a mesoscale lowland river watershed - Hongyu Ding; Jing Su; Yuanyuan Sun; Huibin Yu; Mingxia Zheng; Beidou Xi (Water Research, 2024)

Extraction improvement of ionic liquid-functionalized silica by in situ anion-exchange for online solid-phase extraction of estrogens in honey - Yali Ding; Juanjuan Feng; Mingxia Sun; Yang Feng; Xubo Xin; Min Sun (Food Chemistry, 2024)

Amelioration of the physicochemical properties enhanced the resilience of bacteria in bauxite residues - Zhiwen Dou; Yinghong Sun; Yahui Zhang; Mingxia Wang; Ning Zhang; Aiju Liu; Xinxin Hu (Journal of Hazardous Materials, 2024)

Identification of candidate genes for Fusarium head blight resistance from QTLs using RIL population in wheat - Mingxia Zhang; Peng Jiang; Qun Wu; Xu Han; Junxia Man; Junsheng Sun; Jinlong Liang; Jingchuan Chen; Qi Zhao; Ying Guo; Yanrong An; Haiyan Jia; et al. (Plant Molecular Biology, 2024)

Generation of porcine circovirus type 4 virus-like particles and their use to detect serum antibodies - Zheng Fang; Yabin Tu; Mingxia Sun; Shanghui Wang; Xuehui Cai; Tongqing An; Haiwei Wang (Archives of Virology, 2024)

NiCoNC nanoenzyme enhances the performance of insecticides against Solenopsis invicta by inhibiting the gene expression of P450 - Mingxia He; Tianyi Zhang; Qiushu Chen; Changwei Gong; Jian Pu; Jizhi Yang; Zhiwei Lu; Gehong Su; Chun Wu; Yanying Wang; Mengmeng Sun; Hanbing Rao; et al. (Chemical Engineering Journal, 2023)

Chemiluminescence signal amplification for determination of tetrachlorobenzoquinone based on acidified tungsten disulfide quantum dots - Tong Sun; Hongjie Song; Xiaobo Xie; Mingxia Sun; Yingying Su; Yi Lv (Chemical Engineering Journal, 2023)

Incorporating marine particulate carbon into machine learning for accurate estimation of coastal chlorophyll-a - Jie Niu; Ziyang Feng; Mingxia He; Mengyu Xie; Yanqun Lv; Juan Zhang; Liwei Sun; Qi Liu; Bill X. Hu (Marine Pollution Bulletin, 2023)

Effects of radio frequency thawing on the quality characteristics of frozen mutton - Yanan Sun; Yiming Jia; Mingxia Song; Yan Liu; Le Xin; Xiangwei Chen; Hongfei Fu; Yequn Wang; Yunyang Wang (Food and Bioproducts Processing, 2023)

Oxygen vacancy promoted heterogeneous Fenton-like degradation of sulfamethazine by chlorine-incorporated micro zero-valent iron - Xinfu Chen; Jing Su; Yue Meng; Minda Yu; Mingxia Zheng; Yuanyuan Sun; Beidou Xi (Chemical Engineering Journal, 2023)

Hydrogen-assisted one-pot synthesis of ultrasmall TiC nanoparticles enhancing hydrogen cycling of sodium alanate - Xin Zhang; Yukai Lin; Lingchao Zhang; Zhenguo Huang; Limei Yang; Zhenglong Li; Yaxiong Yang; Mingxia Gao; Wenping Sun; Hongge Pan; Yongfeng Liu (Chemical Engineering Journal, 2023)

Insights into the role of the microbial community lifestyle strategies in variations of the dissolved organic matter molecular composition along an effluent-dominated river - Xing Wang; Minda Yu; Xiaosong He; Jing Su; Beidou Xi; Yuanyuan Sun; Xuemei Fu; Yaojia Wang; Mingxia Zheng (Chemosphere, 2023)

4SC-202 exerts an anti-tumor effect in cervical cancer by targeting PRLR signaling pathway - Huijuan Zhang; Mingxia Li; Huiru Sun; Wen Yang; Mingxia Ye; Hua Li; Yuanguang Meng (Journal of Molecular Histology, 2022)

Identification of serum metabolites enhancing inflammatory responses in COVID-19 - Chen-Song Zhang; Bingchang Zhang; Mengqi Li; Xiaoyan Wei; Kai Gong; Zhiyong Li; Xiangyang Yao; Jianfeng Wu; Cixiong Zhang; Mingxia Zhu; Lei Zhang; Xiufeng Sun; et al. (Science China Life Sciences, 2022)

Spatiotemporal variation of precipitation on a global scale from 1960 to 2016 in a new normalized daily precipitation dataset - Jun Liu; Dongyou Wu; Yue Li; Hongli Ren; Yongtao Zhao; Xiaoyu Sun; Haitao Zhang; Mingxia Ji (International Journal of Climatology, 2022)
Increases in total and extreme precipitation have been investigated worldwide using limited spatiotemporal data based on surface observations and satellite remote sensing during recent decades. However, it remains unclear whether rain gauge daily precipitation records also show a significant increase in global precipitation. In this study, we first apply the transformed version of the penalized maximum F test (“transPMFred”) to homogenize daily precipitation (P) records from 10,629 stations around the world during 1960–2016 from a dataset (GHCN‐CMA) that combines the daily precipitation data from the Global Historical Climatology Network (GHCN‐Daily) dataset and the China Meteorological Administration (CMA), and then utilize the homogenized data to study the frequency of daily precipitation on a global scale. The results indicate that precipitation frequency exhibited significant increasing trends from 1960 to 2016 across most of the globe, except for East Asia. Moreover, the variability of global precipitation frequency was more pronounced in wet regions than dry regions, especially in North America, Europe and East Asia based multiple daily precipitation datasets. The regional average frequency for moderate (30th 90th percentile) precipitation increased in North America and Europe. Changes in precipitation frequency decreased for light (P ≤ 30th percentile) and moderate precipitation but increased for heavy and very heavy precipitation, which mainly occurs in dry regions of Australia. Moreover, precipitation frequency in wet and dry regions of East Asia showed opposite trends, with a decrease in wet regions and an increase in dry regions.

GAS5/METTL14/ESR1 genetic variants are related to the susceptibility of coronary heart disease - Yuxiao Sun; Zhaoyun Cheng; Mingxia Cui; Yan Chen; Ruigang Xie; Guoqing Lu; Chuanyu Gao (Functional & Integrative Genomics, 2022)

Blocking of the PD-1/PD-L1 interaction by a novel cyclic peptide inhibitor for cancer immunotherapy - Wenjie Zhai; Xiuman Zhou; Mingxia Zhai; Wanqiong Li; Yunhui Ran; Yixuan Sun; Jiangfeng Du; Wenshan Zhao; Lingxiao Xing; Yuanming Qi; Yanfeng Gao (Science China Life Sciences, 2021)

A potential new recombinant echovirus 18 strain detected in a 4-year-old child with encephalitis in China in 2019 - Yanjun Kang; Ying Hua; Mingxia Sun; Jun Qian; Pengwei Zhu (Archives of Virology, 2021)

Soil carbon and nitrogen of wheat–maize rotation system under continuous straw and plastic mulch - Yajin Hu; Benhua Sun; Shufang Wu; Hao Feng; Mingxia Gao; Penghui Ma; Tongxun Zhang; Xiaomin Pi (Nutrient Cycling in Agroecosystems, 2021)

Impact of Arctic amplification on declining spring dust events in East Asia - Jun Liu; Dongyou Wu; Guangjing Liu; Rui Mao; Siyu Chen; Mingxia Ji; Pingqing Fu; Yele Sun; Xiaole Pan; Hongchun Jin; Yubin Zhou; Xin Wang (Climate Dynamics, 2020)
Dust aerosols play key roles in affecting regional and global climate through their direct, indirect, and semi-direct effects. Dust events have decreased rapidly since the 1980s in East Asia, particularly over northern China, primarily because of changes in meteorological parameters (e.g. surface wind speed and precipitation). In this study, we found that winter (December–January–February) Arctic amplification associated with weakened temperature gradients along with decreased zonal winds is primarily responsible for the large decline in following spring (March–April–May) dust event occurrences over northern China since the mid-1980s. A dust index was developed for northern China by combining the daily frequency of three types of dust event (dust storm, blowing dust, and floating dust). Using the empirical orthogonal function (EOF) analysis, the first pattern of dust events was obtained for spring dust index anomalies, which accounts for 56.2% of the variability during 1961–2014. Moreover, the enhanced Arctic amplification and stronger Northern Hemisphere annular mode (NAM) in winter can result in the anticyclonic anomalies over Siberia and Mongolia, while cyclonic anomalies over East Europe in spring. These results are significantly correlated with the weakened temperature gradients, increased precipitation and soil moisture, and decreased snow cover extent in the mid-latitude over Northern Hemisphere. Based on the future predictions obtained from the Fifth Climate Models Intercomparison Project (CMIP5), we found that the dust event occurrences may continually decrease over northern China due to the enhanced Arctic amplification in future climate.

Deletion of pseudorabies virus US2 gene enhances viral titers in a porcine cerebral cortex primary culture system - Chuang Lyu; Shuwen Wang; Mingxia Sun; Yandong Tang; Jinmei Peng; Zhijun Tian; Xuehui Cai (Virus Genes, 2018)

Speckle suppression in synthetic aperture radar ocean internal solitary wave images with curvelet transform - Guozhen Zha; Qingyou He; Changlong Guan; Jian Sun; Mingxia He (Acta Oceanologica Sinica, 2016)